ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGELUARAN KONSUMSI PANGAN KELUARGA PETANI DI KECAMATAN BELITANG KABUPATEN OKU TIMUR (JASEP, 2021)
This research was conducted in Juli- September 2021, aimed to measure the amount of household food expenditure and analyze the factors that influence household food consumption in Belitang District, East OKU Regency. The research method used is a survey method to farmer families in Belitang District, namely Karang Kemiri Village and Sidomulyo Village. The sampling method was carried out using the multistage random sampling method, namely sampling using more than one probability sampling technique more efficiently and effectively. The application of the multistage random sampling method uses a cluster sampling technique. The results showed that the average food consumption expenditure of farmer households in Belitang District in one month was Rp. 867,490. Furthermore, based on per capita food consumption, food consumption expenditure in Belitang District is Rp. 213.828, - greater than the Food Poverty Line Index of East OKU Regency, which is Rp. 156,170. Factors that affect food consumption expenditure of farmer households in Belitang District include household income and the number of family members, while the level of education does not affect the amount of household consumption expenditure. Keyword: Food, Consumption, factors